Chinese Migrant Parents and Complementary Schooling in Germany A Sociolinguistic Ethnography - Li-Gottwald, Jiayin (Verlag Barbara Budrich, 2022)
Wie kooperieren Eltern miteinander, welchen Wert messen sie ihrer Interaktion bei und wie hängt der Grad der Kooperation mit dem sozialen Status und zusammen? Die Studie nimmt die sozialen Beziehungen zwischen verschiedenen Gruppen chinesischer Eltern an einer chinesischen Mandarin-Sprachschule in einer Großstadt in Deutschland unter die Lupe. Mit Hilfe eines ethnographischen Ansatzes wird ein lebendiges Bild der elterlichen sozialen Interaktionen innerhalb und außerhalb des chinesischen Schulumfelds gezeichnet. Die Studie zeigt die Bedeutung sozialer Interaktionen auf und erörtert sie im Zusammenhang mit dem sozioökonomischen Hintergrund ihrer Migrationsverläufe; How do parents cooperate with each other, what value do they attach to their interaction and how is the degree of cooperation related to social status? The study takes a close look at the social relationships among various groups of Chinese parents at a Chinese Mandarin language school in a metropolitan city in Germany. Taking an ethnographic approach, it captures a vivid picture of the parental social interactions in and outside the Chinese school setting. The study reveals the significance of social interactions, discussing it in relation to the parents' socioeconomic backgrounds and individual migrant trajectories.